The Role of Religious Education in Promoting Interfaith Dialogue in Multicultural Societies - Indriatama Adjani; Fransisca Oktaviani; Nurul Ulfa (International Forum of Researchers and Lecturers, 2024)
This article explores the role of religious education in fostering interfaith dialogue in multicultural societies. It examines how religious education can cultivate mutual respect, understanding, and cooperation between different religious communities. The study also discusses the pedagogical strategies that can be adopted in religious education to support interfaith dialogue and contribute to social harmony.